Synthesis, In Silico, and Biological Applications of Novel Heteroleptic Copper (II) Complex of Natural Product-Based Semicarbazone Ligands - Fekadu Muleta; Tegene Desalegn (Journal of Chemistry)
Recently, heteroleptic coordination between essential metallic elements with semicarbazone-based derivatives attracts more consideration for the varied ranges of bioactivities. Semicarbazone-based moiety holding azomethine (C=N) group become flexible ligands, forming stable complexes. Through a stirring and reflux technique, a novel heteroleptic complex of copper (II) was synthesized by reacting two semicarbazone-based derivative ligands, ortho-phthalaldehyde disemicarbazone (L1) and dehydrozingerone semicarbazone (L2), with copper chloride salt in 1 : 1 : 1 molar ratio. Magnetic moment measurement, elemental analyzer, thermogravimetric (TGA) analysis, and several spectroscopic techniques were applied to describe the prepared compounds. The disc diffusion and DPPH methods were actually used to investigate the antibacterial and antiradical potentials, respectively. The obtained data indicates the ligand (L1) has good mean inhibition zones on Staphylococcus aureus (12.42 ± 0.00 mm) and S. pyogenes (11.64 ± 0.12 mm) bacteria. The heteroleptic [Cu(L1) (L2)] complex displayed higher antibacterial actions (13.67 ± 0.52 mm) on Streptococcus pyogenes bacteria. The [Cu(L1) (L2)] complex also shows better antiradical potential (63.7%). Furthermore, the docking result of prepared compounds on S. aureus gyrase confirms the ligands (L1 and L2) and the complex potential molecules possess the smallest binding potential of −8.0 to −8.4 kcal/mol. A higher value was achieved by [Cu(L1) (L2)] complex (−8.4 kcal/mol). Thus, this study indicates an insight towards combining semicarbazone form derivatives of natural source origin with a synthetic compound as ligands through metal coordination could enhance bioactivity.